Evangelização ou mercantilização da fé: cotejamento entre sagrado, fé, ética e igreja na modernidade a partir dos estudos sobre a evangelização através do uso da mídia - Maria, Ruben Ferreira (2012)
If we assume that the man has a naturally religious essence and religion, as it is presented to us today; carries the believers to a relational dimension where the natural coexist with supernatural, we are going to conclude that religiosity is located where the human beings live and establish relations. Consequently, nowadays, the, religion is also present in the air" in the technological waves of virtual communication and in the images which are exhaustively shows, given that the media is one of the vehicle for this dissemination. Moreover, there is the fact that during the last decades, the mass media enabled the proliferation of spectacles through the new organizations in the media, such as television and internet. In these organizations, the spectacle itself is becoming one of organizational principles of the daily life and the peculiar contemporary religiosity, thus while we reach the end of this dissertation, we realize that the society of the spectacle, which was presented and defended by Debord in the 1960s and which we are inserted, allows the religiosity propagated by the mass media constitutes itself as a series of technologically sophisticated shows, to meet the expectations of the faithful religious public, who at the first sight, seems to be increasingly hungry for entertainment. Meanwhile, the numerous forms of entertainment invade the modern and multimedia every day, the same extent that enhances the way of the spectacle of the media culture. Thus, we can see that the beginning of the religious life is increasingly shaped by the spectacle. Countless hours of religious content is present on the screens of the media culture, presenting not only the great moments of the daily life filled with represent but also even a richer material for fantasies and dreams, shaping the thoughts behavior, identities and the religions. In this case, the profundity of faith on the spectacular religions not measured by the theological anilities of its postulates but it is measured by the intensity of the individual feeling, who are engaged with the religious fervor experienced in the services that is exactly why, in these services the faithful are taken by attacks of catalepsy convulsions, visions, burst into laughter on sudden outbursts of singing or even barking. In this sense when we approach ours thesis, the relationship between religion, media, spectacle and entertainment, we reflect about the care of the media discourse, potentially dramatic the narratives and characters present on the media, somehow, are dramatized, in order to provoke emotions either laughter or tears.